PEMILIHAN HELM TERFAVORIT DENGAN MADM BERBASIS GUI MATLAB (Studi Kasus : Pemilihan Helm Terfavorit oleh Mahasiswa FSM Undip, Semarang) - Nadya Kiki Aulia; Tatik Widiharih; Abdul Hoyyi (Jurnal Gaussian, 2017)
Safety is an important factor that need to be considered in driving safety. One of important factor that need to be considered is the use of Indonesian National Standard (SNI) helmets. The large number of SNI helmets existance, make consumers especially students, have their own preferences in choosing a helmet. The methods that can be used to choose the most favorite helmet is ELECTRE and TOPSIS. Both of these methods are the methods used to solve MADM problems. There are 8 brands of helmets namely INK, KYT, BMC, HIU, VOG, BOGO, NHK, dan GM. For helmet selection criteria are safety helmets (helmet safety straps when worn), affordable helmet prices, easy found helmet, variety of helmet colors, various sizes available, helmets cover the entire face, comfortable helmet glass when worn, clear helmet glass, quality of the outside of the helmets, helmet foam quality, and resistance to impact. By using ELECTRE method, this research got result that the most favorite helm is INK helmet brand which has the number of row element as much 5. For TOPSIS method, the most favorite helmet is KYT helmet brand with preference value equal to 0.7146. Keywords: ELECTRE, TOPSIS, Helmet, favorite, GUI